For Xmas: Motor Cars an' all Zorts for the Childern – Commodification of Devonshire Speech in 20th-century Periodicals - Tissens, René (Complutense Journal of English Studies, 2026)
This paper addresses the early commodification of Devonshire dialect in provincial newspapers from a revisionist third-wave sociolinguistic perspective. Johnstone (2009), in the case of Pittsburghese, has shown how locally imagined varieties are circulated via metapragmatic practices that create public awareness about a linguistic variety and index a series of social meanings. During the 19th century, the speech of Devonshire was widely circulated in fiction, drawing attention to a set of frequent linguistic features that were commented upon by natives and non-natives of the dialect. While interest in Devonshire dialect writing in fiction declined over time after the turn of the century, this paper shows how those same recurrent linguistic features were used with a commercial intent in advertisements published in two provincial newspapers, the North Devon Journal (1929) and the North Devon Herald (1930). The commodification of the dialect during the first half of the 20th century seems to prove that Devonshire speech was still enregistered as well as associated with a specific characterological figure: the farmer.
Keywords: Commodification; Devonshire; third-wave sociolinguistics; twentieth-century